Cognitive Dysfunction Is Associated with Greater Imbalance and Falls in Essential Tremor - Louis, Elan D.; Kellner, Sarah; Morgan, Sarah; Collins, Kathleen; Rohl, Brittany; Huey, Edward D.; Cosentino, Stephanie (Frontiers in Neurology, 2017)
Background: Essential tremor (ET) is not exclusively a tremor disorder; it is also associated with cognitive and gait dysfunction. However, a gap in knowledge is that the relationship between cognitive and gait dysfunction has not been studied in detail in ET. We examined the relationship between cognition and balance and falls in ET, and hypothesized that cognitive dysfunction in ET patients would be associated with greater problems with balance and more falls. Methods: ET cases were recruited into the Clinical-pathological Study of Cognition in Essential Tremor. A comprehensive cognitive assessment was performed. This included the Montreal Cognitive Assessment (MoCA) to measure global cognition, multiple motor-free tests comprehensively assessing performance in each cognitive domain, and an assignment of Clinical Dementia Rating (CDR) scores. We collected data on the number of reported falls in the past year, and balance confidence was assessed using the six-item Activities of Balance Confidence Scale. These cross-sectional analyses utilized baseline data. Results: There were 199 ET cases (mean age 78.6 years). In linear regression models that considered the effects of numerous confounding variables, lower global cognition (poorer cognition) was associated with greater number of falls and reduced balance confidence (p<0.05). In similar adjusted linear regression models, higher CDR score (poorer functional cognition) was associated with greater number of falls and reduced balance confidence (p<0.05). We also assessed whether number of falls and balance confidence was associated with performance in specific cognitive domains. Number of falls was most closely linked with performance on tests of executive function, and balance confidence, with executive function, attention and memory. Conclusions: These data indicate that a correlate of poorer cognition in ET is greater number of falls and lower balance confidence. Cognition should enter the dialog with ET patients as an issue of clinical significance.